Upaya Kepolisian Dalam Menanggulangani Tindak Pidana Perdagangan Orang: Studi Kasus Polda NTT - Chatarina Seina Marina Moses Dando; Deddy R. Ch. Manafe; Adrianus Djara Dima (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study aims to find out and analyze the efforts made by the East Nusa Tenggara Provincial Police (Polda NTT) in tackling the crime of human trafficking in NTT Province. This type of research is an empirical research using primary data and secondary data collected using interviews and literature studies that are analyzed qualitatively descriptively. The results of this study show (1) the efforts made by the NTT Police in tackling human trafficking in NTT Province, namely Pre-Emptive efforts, Preventive efforts and Repressive efforts (2) obstacles faced by the police in tackling the crime of human trafficking, namely the number of perpetrators who are not detected and parents who are slow to report, the difficulty of the police in collecting evidence in prosecuting the perpetrators and the inability of the victims to Saying the truth is because the victim is afraid of things that can be dangerous.